Pengaruh Paduan Serbuk Fe12% pada Aluminium terhadap Porositas dan Struktur Mikro dengan Metode Gravity Casting - Sumpena Sumpena (Jurnal Engine: Energi, Manufaktur, dan Material, 2017)
The purpose of this research is to know the effect of Fe12% powder alloy on aluminum to porosity and micro structure by gravity casting method. Metal Matrix Composite (MMC) is an engineering material formed from the combination of two or more materials to obtain new materials with better properties. Making of composite material with aluminum matrix or metal matrix composite (MMC) can be done by casting method. The composite forming elements are called boosters (fibers or particles) and binders (matrices). In the process of casting metal can occur porosity In the casting process with sand molds usually occur porosity, causing the mechanical properties of casting objects decreased. Porosity is caused by bubbles of gas, gas released by the core when exposed to metal liquid heat, resulting in pores or perforated defects.The process of smelting was carried out at the metal foundry laboratory of Mechanical Engineering UP 45 Yogyakarta. The smelting process uses a krusible furnace with coke fuel, on which it is placed kowi to place aluminum and iron powder to be melted. Aluminum and 12% iron powder are weighed in accordance with the volume of the pattern, so that the melt does not suffer from metal deficiency. Observation of porosity is done by looking visually on each side of the outer part of the casting object. Observation of microstructure using optical microscope is done by taking three samples of specimen castings that have been in the preparation of polishing machine and etching. The effect of Fe 12% alloys on porosity is the average porosity occurring on specimens A, B and C of 2,766 gr / cm3. The effect of Fe 12% alloys on micro structure is the spreading of Fe, Si and Mg elements evenly, but for the C specimens of Fe and Si bersenyawa, while the Al and Mg elements are separate.